Dermatologic toxicities to immune checkpoint inhibitor therapy: A review of histopathologic features - Ellis, Samantha (J Am Acad Dermatol, 2020)
Antineoplastic agents that utilize the immune system have revolutionized cancer treatment. Specifically, implementation of immune checkpoint inhibitors, monoclonal antibodies that block cytotoxic T lymphocyte-associated antigen-4 (CTLA-4), programmed cell death protein 1 (PD-1), or programmed death ligand 1 (PD-L1), show improved and sustained responses in cancer patients. However, these agents are associated with a plethora of adverse events, many manifesting in the skin. As the clinical application of cancer immunotherapies expands, understanding the clinical and histopathologic features of associated cutaneous toxicities becomes increasingly important to dermatologists, oncologists, and pathologists to ensure timely diagnosis and appropriate care. This review discusses cutaneous reactions to immune checkpoint inhibitors, focusing on histopathologic features.